(untitled) (Hekima Review, 2005)
The case of these boys and girls abducted to be made child soldiers by the Lord’s Resistance Army (LRA) is the situation of thousands of children all over the world, “boy or girl- under the age of 18, compulsorily, forcibly or voluntarily recruited or used in hostilities by armed forces, paramilitaries, civil defense units or other armed groups.